PENGARUH STRUKTUR MODAL TERHADAP PAJAK PENGHASILAN BADAN TERUTANG : STUDI EMPIRIS PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Mei Hotma Mariati Munte (Jurnal Bina Bangsa Ekonomika, 2024)
This study aims to test and analyze the influence of capital structure (long-term debt to asset ratio (LDAR) and debt to equity ratio (DER)) on income tax of payable entities, both partially and simultaneously. The type of research is quantitative research. This study uses secondary data in the form of an annual report for the period of 2017 to 2020 obtained from the Indonesia Stock Exchange (IDX) by accessing the www.idx.co.id website. The sampling technique used was purposive sampling by obtaining a number of 12 manufacturing companies in the food and beverage sub-sector that became the research sample. Based on the results of the study, it is found that LDAR (X1) partially has a positive and significant effect on corporate income tax payable (Y) in manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX), while DER (X1) has a positive and significant effect on corporate income tax payable (Y). Simultaneously, LDAR (X1) and DER (X2) together have a positive and significant effect on corporate income tax payable (Y) in manufacturing companies in the food and beverage sub-sector listed on the IDX